Clinical Characteristics of Patients With HNF1-alpha MODY: A Literature Review and Retrospective Chart Review - Zhao, Qinying; Ding, Li; Yang, Ying; Sun, Jinhong; Wang, Min; Li, Xin; Liu, Ming (Frontiers in Endocrinology, 2022)
The clinical manifestation of hepatocyte nuclear factor-1-alpha (HNF1-alpha) maturity-onset diabetes of the young (MODY) is highly variable. This study aims to investigate the clinical characteristics of patients with HNF1-alpha MODY in general, by geographical regions (Asian or non-Asian), HNF1-alpha mutations, and islet autoantibody status. A literature review and a chart review of patients with HNF1-alpha MODY were performed. The means and proportions from studies were pooled using the inverse variance method for pooling, and subgroup analyses were performed. A total of 109 studies involving 1,325 patients [41.5%, 95% confidence interval (CI): 35.2, 48.1; male] were identified. The mean age of diagnosis was 20.3 years (95% CI: 18.3–22.2), and the mean glycated hemoglobin was 7.3% (95% CI: 7.2–7.5). In comparison, Asian patients exhibited significantly higher HbA1c (p = 0.007) and 2-h post-load C-peptide (p = 0.012) levels and lower levels of triglyceride (TG) (p < 0.001), total cholesterol (TC) (p < 0.001), and high-density lipoprotein cholesterol (HDL-c) (p < 0.001) and less often had macrovascular complications (p = 0.014). The age of diagnosis was oldest in patients with mutations in the transactivation domain (p < 0.001). The levels of 2-h post-load C-peptide (p < 0.001), TG (p = 0.007), TC (p = 0.017), and HDL-c (p = 0.001) were highest and the prevalence of diabetic neuropathy was lowest (p = 0.024) in patients with DNA-binding domain mutations. The fasting (p = 0.004) and 2-h post-load glucose (p = 0.003) levels and the prevalence of diabetic neuropathy (p = 0.010) were higher among patients with positive islet autoantibodies. The study demonstrated that the clinical manifestations of HNF1-alpha MODY differed by geographical regions, HNF1-alpha mutations, and islet autoantibody status.